Mechanism of catalytic ozonation in expanded graphite aqueous suspension for the degradation of organic acids - Song, Yang (Environmental technology, 2023)
In this study, expanded graphite (EG) was prepared by the oxidation and intercalation of the natural flake graphite using perchloric acid and potassium permanganate at different expansion temperatures (300, 400, 500, and 600°C), and were characterized by scanning electron microscope (SEM) and X-ray photoelectron spectroscopy (XPS). EG prepared at 500°C was found to be highly effective for the mineralization of oxalic acid aqueous solution during ozonation at pH 3, which was ascribed to the formation of hydroxyl radicals from the surface reaction of surface hydroxyl groups on EG with ozone. The performance of expanded graphite in this catalytic system was basically unchanged after three repeated use. The presence of Cl-, SO42-, HPO42-/H2PO4- and NO3- could inhibit the degradation of oxalic acid in catalytic ozonation with EG. Degradations of oxamic acid and pyruvic acid in catalytic ozonation with EG were pH-dependent, which were lower than that of oxalic acid. The degradations of oxalic acid and oxamic acid were identified as mineralization process by the determination of TOC, while pyruvic acid may transform into organic products such as acetic acid by O3/EG. Manganese ion (Mn2+) could promote the degradation of oxalic acid by O3/EG at pH 3 because permanganate was produced by O3/EG in oxalic acid solution and then reacted with oxalic acid readily at acidic pH. Catalytic ozonation by EG exhibited great application potential for the destruction of refractory organic compounds